KOMBINASI SENAM MATA DAN KOMPRES DINGIN TERHADAP KELELAHAN MATA PADA MAHASISWA STIKES KARYA HUSADA KEDIRI - Nithalia Ivada; Efa Nuraini; Didit Damayanti (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Computer Vision Syndrome or someone who has complaints when doing activities with computers that are too long. Because the use of eye muscles that require high concentration can cause eye fatigue. Eye fatigue can be overcome by giving eye exercise therapy and cold compresses. This study aims to prove that the combination of eye exercises and cold compresses can overcome eye fatigue. This study used a Quasy Experimental research design with a pretest-posttest control group design method. The research population of undergraduate nursing students was 79 students and the sample consisted of 24 respondents who were selected using the purposive sampling technique which was divided into 2 groups, namely the treatment group and the control group. Data collection using an eye fatigue questionnaire. Based on the results of posttest research in the treatment group, all respondents (100%) experienced mild fatigue. While in the post-test control group half of the respondents (50%) experienced severe fatigue. Data analysis used the Mann-Whitney test with results in the treatment group and posttest control group (0.000 < 0.05). That the combination of eye exercises and cold compresses are given 4 times in 2 weeks can reduce eye fatigue by training the eye muscles and providing a relaxing effect. It is recommended for students to rest their eyes with the 20-20-20 rule and implement a combination therapy of eye exercises and cold compresses to reduce eye fatigue.